2020
DOI: 10.3389/fphar.2020.557629
|View full text |Cite|
|
Sign up to set email alerts
|

Does Lithium Deserve a Place in the Treatment Against COVID-19? A Preliminary Observational Study in Six Patients, Case Report

Abstract: Lithium has shown the capacity to: a) inhibit the replication of several types of viruses, some of which are similar to the SARS-CoV-2 virus, b) increase the immune response by reducing lymphopenia, and c) reduce inflammation by preventing or reducing the cytokine storm. In the present study, we have treated six patients with severe COVID-19 infection with lithium carbonate. We found that lithium carbonate significantly reduced plasma reactive C-Protein levels, increased lymphocyte numbers and decreased the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 30 publications
1
32
0
3
Order By: Relevance
“…In a recent preliminary observational study, six patients with severe COVID-19 were treated with lithium carbonate. Those patients showed decreased reactive C-protein, increased lymphocyte numbers, and a decreased neutrophil-lymphocyte ratio [81]. This is consistent with the immunomodulation of lithium, and possibly with the other actions proposed in this paper.…”
Section: Covid-19 Patients On Lithium: Expectations Probabilities and The Anti-viral Action Of Lithiumsupporting
confidence: 90%
See 1 more Smart Citation
“…In a recent preliminary observational study, six patients with severe COVID-19 were treated with lithium carbonate. Those patients showed decreased reactive C-protein, increased lymphocyte numbers, and a decreased neutrophil-lymphocyte ratio [81]. This is consistent with the immunomodulation of lithium, and possibly with the other actions proposed in this paper.…”
Section: Covid-19 Patients On Lithium: Expectations Probabilities and The Anti-viral Action Of Lithiumsupporting
confidence: 90%
“…Thus, if lithium is considered in COVID-19, it is important to assess the feasibility of using different routes of administration in patients who cannot tolerate the oral form. One possible way to involve oral lithium in such patients is to start with the conventional management of COVID-19 until the patients are stabilized and can take lithium orally [81].…”
Section: The Relevant Safety Of Lithium and Its Administrationmentioning
confidence: 99%
“…11. 10.3389/fphar.2020.557629 The manuscript by Spuch et al, provides interesting preliminary data in support of a possible role of lithium the treatment of patients with COVID-19 (Spuch et al, 2020). Although limited to six patients treated with different additional therapeutic approaches, it was encouraging that the authors found the lithium carbonate increased lymphocyte numbers, reduced plasma reactive C-Protein levels while decreasing the neutrophil-lymphocyte ratio used as a measure for severe disease.…”
Section: A Commentary Onmentioning
confidence: 97%
“…Does Lithium Deserve a Place in the Treatment Against COVID-19? A Preliminary Observational Study in Six Patients, Case Report by Spuch, C., López-García, M., Rivera-Baltanás, T., Rodrígues-Amorím, D., and Olivares, J. M. (2020). Does lithium deserve a place in the treatment against COVID-19?…”
Section: A Commentary Onmentioning
confidence: 99%
“…Recently, Pietruczuk et al [ 167 ] demonstrated that T lymphocytes of patients suffering from bipolar disorder that were treated with lithium or valproate, are characterized by pro-inflammatory activity, decreased proliferative activity and increased susceptibility to apoptosis. Finally, a case report by Spuch et al [ 317 ] showed that lithium carbonate improved inflammatory activity and immune response in patients with severe SARS-CoV-2 infection.…”
Section: Adjunctive Psychotropic Treatments During Sars-cov-2 Infectimentioning
confidence: 99%